Accelerating the Empowerment of Madrasah - Jajat Burhanudin (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2000)
The empowerment of madrasah (Islamic school) is an important agenda item for the Indonesia Ministry of Religious Affairs (MORA). As the formal body overseeing madrasah education, MORA has taken many strategic steps to improve the quality of madrasah schooling. These steps have been taken in response to demand for the improvement of madrasah education aiming to produce graduates who can compete with graduates of other institutions, particularly public schools under the management of the Ministry of Education. In recent years, MORA has be able to intensify, its efforts to improve the quality of madrasah as a result of loans made available by the Asian Development Bank (ADB) specifically for this purpose. The ADB loans, as a component the Basic Education Project, aims to improve the quality of basic education in madrasah in 15 districts within 5 provinces.DOI: 10.15408/sdi.v7i2.714